Biometric and ultrasonographic evaluation on mammary gland of goat - KUMAR, VIPUL; BANSAL, NEELAM; UPPAL, VARINDER; GUPTA, ANURADHA (The Indian Journal of Animal Sciences, 2024)
Gross and ultrasonographic studies were conducted on the mammary gland of goat (n=18 for each study) during pre-pubertal, lactating and non-lactating stages. Mammary gland was located into the inguinal region and divided into two halves by mammary groove which was prominent during lactation stage. Each halve had separate glandular body and conical teat divisible into tip, mid and base regions. The mammary gland contained numerous lactiferous ducts which opened into the gland sinus that continued distally as teat sinus and teat canal. The gland sinus and teat sinus were separated from each other by annular folds, which were more prominent in lactating animals. At the junction of teat sinus and teat canal, small mucosal elevation was observed as Furstenberg’s rosette. Teat wall was lined by skin, teat internal mucosal layer and teat sinus from outside to inside. Ultrasonographic observations showed that the lactating mammary gland contained an echogenic structure of variable size indicating gland sinus, lactiferous ducts, blood vessels, glandular parenchyma, while the homogenous echogenic component depicting more connective tissue stroma in non-lactating and pre-pubertal goat. The teat wall was made up of innermost hyperechogenic layer (teat mucosa), middle hypoechogenic (fibromuscular) layer and mild hyperechogenic teat skin. Teat sinus was anechogenic, however teat canal was demarcated by hyperechogenic streak. Biometrical and ultrasonographic observations were recorded on teat canal length, maximum diameter of teat, maximum teat wall thickness. Present study showed that there was no significant difference in biometric and ultrasonographic measurements of goat teat. Therefore, it may be concluded that the gross and ultrasonographic observations may be used to diagnose any abnormality in the udder during clinical examination.